Representation of Science in Two Realistic Novels of Different Cultures - K. Akhmedova, Aziza; D. Muratova, Elmira (International Journal of Psychosocial Rehabilitation, 2020)
Given the expansion of realistic novels just before the World War II, this article analyzes the representation of science in American and Uzbek novels. A close reading of Arrow smith by Sinkler Lewis and The Three Roots by Pirimkul Kodirov shows that the authors’ approach to create realistic characters of science sphere bear similarities. A careful analysis is given to the interplay of facts and fiction in the novels, the representation of the authors’ aesthetic ideals by means of protagonists and the tools that enable the creators to achieve realistic description of characters. As a result of the comparison, the type of literary relations between the two national literatures in the mentioned period is clarified and the similarity of the two novels explained. It is concluded that similarities of the novels are both a result of mediated form of internal contact and typological affinities.